INVESTIGATING DRIVERS OF DIGITAL BANKING ADOPTION OF GEN Z IN INDONESIA - Supriyadi, Fortuna Tunggadewi; Darwanto, Darwanto (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
Despite the fact that digital banks are the most recent financial service that provides online banking services without direct contact with customers, they have yet to transform the whole financial sector. This study was done in a quantitative manner utilizing primary data to investigate drivers of digital banking adoption by Gen Z using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) approach. There was a total of 232 respondents participating in this study. The data was analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results show that social influence, facilitating conditions, hedonic motivations, perceived value, and habit positively influence the Gen Z